1988
DOI: 10.1099/0022-1317-69-10-2701
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of Mouse Interferon Alpha Species: MuIFN- 10, a Subspecies with Low Antiviral Activity

Abstract: It has been drawn to our attention that the DNA sequence of the MulFN-~10 gene published in this paper is almost identical to one previously published for the MulFN-~7 gene [Dion, M., Vodjdani, G. & Doly, J. (1986). Sequence and expression of a novel murine interferon alpha gene -homology with enhancer elements in the regulatory region of the gene. Biochemical and Biophysical Research Communications 138,[826][827][828][829][830][831][832][833][834]. There is one sequence difference in the 5' non-coding regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This band was not observed in conditioned medium from cells ttansfected with empty plasmid and likely represents a glycosylated form of mIFN-a. Recombinant mIFN-aA ran with an approximate molecular mass of 18 kDa, which corresponds to the predicted molecular weight of nonglycosylated mIFN-a (Van Heuvel et al, 1986;Trapman et al, 1988). Assay of conditioned medium using an anti-viral bioassay for mIFN-a indicated that approximately 175 X 10^ IU of mlFNa was present per milliliter (Fig.…”
Section: Expression Of Mifn-amentioning
confidence: 96%
“…This band was not observed in conditioned medium from cells ttansfected with empty plasmid and likely represents a glycosylated form of mIFN-a. Recombinant mIFN-aA ran with an approximate molecular mass of 18 kDa, which corresponds to the predicted molecular weight of nonglycosylated mIFN-a (Van Heuvel et al, 1986;Trapman et al, 1988). Assay of conditioned medium using an anti-viral bioassay for mIFN-a indicated that approximately 175 X 10^ IU of mlFNa was present per milliliter (Fig.…”
Section: Expression Of Mifn-amentioning
confidence: 96%
“…They are coded by an intronless multigene family clustered on murine chromosome 4 and in human chromosome 9. One IFN-␤ and multiple IFN-␣ genes were found in the mouse and human genomes (11,13,14,15,22,25,30,35,37,39,41,44,47,50). Other IFN-␣/␤ genes described include the murine limitin gene and the human IFN-gene, as well as the IFN-and IFN-ε/ genes that were found in both the human and murine genomes (Table 1) (2,9,24,32,46).…”
mentioning
confidence: 99%
“…Three of the EcoRI fragments (7, 5-5 and 4 kb) carry distinct MuIFN-~ genes. The 5.5 kb EcoRI fragment contains the previously described MuIFN-~7(10) gene (Dion et al, 1986;Trapman et al, 1988), and another IFN-~ gene located in the 7 kb fragment is currently under study. As expected, these results confirm that the MuIFN-~ genes consist of a In the flanking regions of MulFN<(8 all the features necessary for induction and efficient transcription are present; we therelbre studied its induction in C243 ceils by RNase protection analysis of the transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…So far nine different genes and a pseudogene have been isolated and characterized (Shaw et al, 1983;Daugherty et al, 1984;Kelley & Pitha, 1985a;Le Roscouet et al, 1985;Zwarthoff et al, 1985;Dion et al, 1986;Seif& De MaeyerGuignard, 1986;Trapman et al, 1988); all except the pseudogene encode biologically active proteins.…”
Section: Introductionmentioning
confidence: 99%